2020
DOI: 10.1016/j.jot.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory meta-analysis on dose-related efficacy and complications of rhBMP-2 in anterior cervical discectomy and fusion: 1,539,021 cases from 2003 to 2017 studies

Abstract: s Background/Objective Anterior cervical discectomy and fusion (ACDF), commonly using autogenous iliac bone graft may be limited by donor site availability, donor-site morbidity, lower fusion rate among specific patients and longer surgical time. Surgeons used rhBMP-2 as an alternative in order to fill these clinical needs. However, studies comparing with and without rhBMP-2 in ACDF have reported conflicting results on efficacy and complications. Therefore, the purpose of this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…13,14 BMP-2, on the other hand, is critical during the stages of chondrogenesis and osteogenesis. 15 Research to determine a safe dose of BMP-2 is still ongoing. Bone Morphogenetic Protein-2 activates SMAD signaling in vitro and animal cells dosedependent.…”
Section: Bmp-2 Involvement In Osteogenesismentioning
confidence: 99%
“…13,14 BMP-2, on the other hand, is critical during the stages of chondrogenesis and osteogenesis. 15 Research to determine a safe dose of BMP-2 is still ongoing. Bone Morphogenetic Protein-2 activates SMAD signaling in vitro and animal cells dosedependent.…”
Section: Bmp-2 Involvement In Osteogenesismentioning
confidence: 99%
“…As a result of numerous clinical trials from 2002 to 2017 to assess the safety, efficacy and dose-dependent effects of INFUSE® implantation in interbody fusion using recombinant BMP-2 and a collagen sponge had a significantly higher fusion rate compared to patients without recombinant BMP-2 [57,58].…”
Section: Synthetic Polymers Are Also Promising Materialsmentioning
confidence: 99%
“…INFUSE ® Bone Graft consists of rhBMP-2 (1.5 mg/mL) and ACS as a carrier. Multiple clinical trials conducted from 2002 to 2017 to evaluate the safety, efficacy and dose-dependent effects of INFUSE ® implantation in anterior cervical discectomy and fusion (ACDF) demonstrated that patients treated with rhBMP-2/ACS had significantly higher fusion rates compared to non-rhBMP-2 patients, not only in total value but also in 3 tiers of rhBMP-2 doses [168]. It should be noted that ACS loaded with a low dose of rhBMP-2 (<0.7 mg/level) showed the highest fusion rate among all rhBMP-2 doses.…”
Section: Clinical Trials Of Polymer-based Drug Delivery Systems For B...mentioning
confidence: 99%